Climate change in Asia and the Pacific how can countries adapt? - Anbumozhi, Venkatachalam; Breiling, Meinhard; Pathmarajah, Selvarajah; Reddy, Vangimalla R (SAGE, 2012)
This volume examines the framework conditions for integrating climate change adaptation measures into agriculture, water, and natural resources management activities for the Asia and Pacific region. Based on the review of country experiences, the book describes key dimensions, suggests interventions for further exploration, and serves as a basis for planning and mainstreaming climate change adaptation into sectoral planning